2000
DOI: 10.1128/aem.66.9.4022-4028.2000
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Genes in Environmental Strains of Vibrio cholerae

Abstract: The virulence of a pathogen is dependent on a discrete set of genetic determinants and their well-regulated expression. The ctxAB and tcpA genes are known to play a cardinal role in maintaining virulence in Vibrio cholerae, and these genes are believed to be exclusively associated with clinical strains of O1 and O139 serogroups. In this study, we examined the presence of five virulence genes, including ctxAB and tcpA, as well as toxR and toxT, which are involved in the regulation of virulence, in environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
123
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 154 publications
(134 citation statements)
references
References 42 publications
9
123
2
Order By: Relevance
“…2/40 (5) Vibrio cholerae pathogenicity island EVC4 was considered as being of tcpA 2 /ctxB + genotype supporting the suggestion that not all CT positive V. cholera strains are TCP positive, since TCP is known to be receptor for CTX phage (Chakraborty et al, 2000). The findings reported here are supported by those of Karaolis et al (2001) who demonstrated that the central region of the VPI of tcpA contains most of the divergence between the VPIs of the 6th (classic) and the 7th (El Tor) pandemic strains.…”
Section: Ljf-vpir Aldaf-tagar Vpi2f-r Vpi3f-r Vpi4f-r Vpi5f-r Tcpif-qmentioning
confidence: 62%
See 1 more Smart Citation
“…2/40 (5) Vibrio cholerae pathogenicity island EVC4 was considered as being of tcpA 2 /ctxB + genotype supporting the suggestion that not all CT positive V. cholera strains are TCP positive, since TCP is known to be receptor for CTX phage (Chakraborty et al, 2000). The findings reported here are supported by those of Karaolis et al (2001) who demonstrated that the central region of the VPI of tcpA contains most of the divergence between the VPIs of the 6th (classic) and the 7th (El Tor) pandemic strains.…”
Section: Ljf-vpir Aldaf-tagar Vpi2f-r Vpi3f-r Vpi4f-r Vpi5f-r Tcpif-qmentioning
confidence: 62%
“…For autoagglutination, all strains were grown in LB (pH 6.8) supplemented with 1 % (w/v) NaCl and incubated at 37 uC for 18 h (Chakraborty et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…A DNA probe study showed that a small percentage of environmental strains of V. cholerae non-O1 have the ctx gene (Nair et al 1988). Virulence genes including ctxAB were found among environmental strains from Calcutta, India (Chakraborty et al 2000). Occurrence of ctxA was found among 10% on non-O1/non-O139 environmental isolates from Brazil (Rivera et al 2001).…”
Section: Resultsmentioning
confidence: 97%
“…1,36 In other countries, virulence genes, including tcpA, have been found in V. cholerae non-O1/O139 from the environment, notably in cholera-endemic areas. 37,38 Although initial PCR results suggested these strains carried El Tor and classical tcpA alleles, sequence determination of the tcpA gene and phylogenetic analysis showed that the alleles were related to (but different from) the prototypical alleles (Supplemental Figure S2). The ctxA-negative isolates were also positive by PCR for different alleles of rstR, suggesting they could each possess a different variant of pre-CTX prophage (the CTX prophage devoid of the ctxAB genes).…”
Section: Discussionmentioning
confidence: 99%